Understanding Technology Acceptance in Higher Education Institutions: A Comparative Study of Teacher and Student Perspectives in Lucknow - Ms Runita Sahai Marwah; Dr Bineet Kumar Gupta (Educational Administration: Theory and Practice, 2024)
Understanding Technology Acceptance (TA) in higher education is vital in today’s information-driven era, as rapid technological advancements reshape educational landscapes. Effective evaluation of factors influencing technology adoption is essential to ensure that new innovations are successfully integrated and not wasted. Therefore, to address this gap, the study explores the critical factors influencing TA in Higher Education Institutions (HEIs) from the perspectives of both teachers and students in Lucknow and also assesses the associations between these two groups. An exploratory research design with a quantitative approach was used and primary data was collected from a sample of 461 teachers & 546 students of government and private HEIs in Lucknow using quota sampling. The research tool was constructed and validated and then administered to the respondents in both online and offline mode. Data analysis included factor analysis & chi-square tests using SPSS version 25. The study revealed that two primary factors influence teachers’ acceptance of technology: the perceived value of investing time and energy in learning new tools and their ease of use, which enhances teaching effectiveness. Similarly, students’ acceptance is driven by the ease of learning new tools and their time-saving benefits, alongside awareness and actual use of technology for academic purposes. These findings indicate that enhancing awareness and providing training on technology tools can boost acceptance among teachers and students. Institutions should focus on strategies that highlight the benefits and necessity of technology integration to improve academic performance.